Drug‐induced cutaneous pseudolymphoma: A systematic review of the literature. (4th November 2022) - Etesami, Ifa; Kalantari, Yasamin; Tavakolpour, Soheil; Mahmoudi, Hamidreza; Daneshpazhooh, Maryam
Abstract: Drug‐induced cutaneous pseudolymphoma (CPL) is a common form of pseudolymphoma and there are numerous drugs associated with it. In this study, we performed a systematic review of the literature by searching PubMed/Medline and Embase databases to determine the most common drugs responsible for CPL and to define the demographic, clinical, histopathological and immunopathological characteristics of patients (updated on 30 December 2020). From 883 initially found articles, 56 studies (89 reported cases) were included. The mean age of patients was 54.4 ± 17.7 (ranging 8–86) years, and 46 (51.7%) were men. The median time interval between drug intake and CPL occurrence was 120 days (range 1–7300 days). The shortest median time interval between taking the drug and the onset of the disease was observed among patients taking antidepressants (60 days) (range 7–540) and the longest median time interval was observed in individuals using immunomodulators (300 days) (range 3–7300). The most‐reported drug categories causing CPL were anti‐hypertensives (17.9%), anticonvulsants (14.6%), monoclonal antibodies (13.4%) and antidepressants (11.2%). Moreover, the most common drugs were phenytoin (6.7%), amlodipine (5.6%), fluoxetine (5.6%) and carbamazepine (4.4%). Histopathological evaluation of 76 cases revealed 62 (81.5%) reports of T‐cell infiltrations. Furthermore, positive reports of CD4 (94.0%), CD8 (93.0%) and CD30 (87.5%) were noted. The lowest prevalence of CD30‐positive reports was observed among monoclonal antibodies. In conclusion, anti‐hypertensives, anti‐convulsants, monoclonal antibodies and anti‐depressants are the most common drugs responsible for CPL. It mostly presents in middle‐aged patients with almost no gender difference as pruritic papules, nodules and plaques.